2017
DOI: 10.1681/asn.2017010041
|View full text |Cite
|
Sign up to set email alerts
|

Home Dialysis in the Prospective Payment System Era

Abstract: The ESRD Prospective Payment System introduced two incentives to increase home dialysis use: bundling injectable medications into a single payment for treatment and paying for home dialysis training. We evaluated the effects of the ESRD Prospective Payment System on home dialysis use by patients starting dialysis in the United States from January 1, 2006 to August 31, 2013. We analyzed data on dialysis modality, insurance type, and comorbidities from the United States Renal Data System. We estimated the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 34 publications
(45 reference statements)
0
47
0
Order By: Relevance
“…Recent work has shown upward trends in patient PD utilization after implementation of Medicare PPS for dialysis (31)(32)(33)(34). Results of our study indicate a concurrent increase in PD provision in dialysis facilities after the payment reform.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Recent work has shown upward trends in patient PD utilization after implementation of Medicare PPS for dialysis (31)(32)(33)(34). Results of our study indicate a concurrent increase in PD provision in dialysis facilities after the payment reform.…”
Section: Discussionmentioning
confidence: 52%
“…Recent work has shown upward trends in patient demand for PD (31)(32)(33)(34), with little consideration of changes in facility supply of PD that underlie these patient-level trends. Dialysis facility response to PPS is an important factor in these changes, because payment reform is designed to drive supply-side change in dialysis modality and PD provision.…”
Section: Introductionmentioning
confidence: 99%
“…USRDS data analysis from 1977 to 2015 showed that the use of PD decreased annually since 1977 when it was 16%, to approximately 13% in 1997. With the introduction of incentives from Medicare to cover costs of training for home therapies, this trend reversed and a rapid growth in the number and proportion of ESRD patients who were treated with PD ensued . The combined proportion of incident PD and home hemodialysis was 10.2% in 2013; representing a 52% increase from 2003 and 71% higher than at its nadir in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Medicare to cover costs of training for home therapies, this trend reversed and a rapid growth in the number and proportion of ESRD patients who were treated with PD ensued. 29 The combined proportion of incident PD and home hemodialysis was 10.2% in 2013;…”
Section: Discussionmentioning
confidence: 99%
“…11 Although recent policy changes have helped improve the use of home therapies, including home HD and PD, these 2 modalities remain underused and further steps are still critically needed to continue to expand their use. 20 For example, we need to continue to improve our renal fellows' education on home dialysis therapies, with longitudinal exposure to these modalities (home HD and PD) on an outpatient basis as part of their outpatient nephrology clinical experience. We also need to further refine and improve on our patients' dialysis education programs, making sure that every patient with ESRD is informed about his or her renal replacement therapy options (including kidney transplantation and types of dialysis modality) and also to incorporate a discussion about palliative care when appropriate.…”
mentioning
confidence: 99%